50 years after the exclusion of homosexuality from the Diagnostic and Statistical Manual of Mental Disorders (DSM) - Cruzado, Lizardo (2024)
It is half a century since the historical event constituted by the removal of homosexuality as a psychiatric diagnosis from the North American Diagnostic and Statistical Manual of Mental Disorders (DSM). Although it is a short period of time, it is hard to believe that fifty years ago, homosexual people lacked many basic civil rights in the United States and various laws criminalized private, freely consented sexual acts between adults. Recalling these significant events in the context of a summarized conceptual history of homosexuality is the main objective of this brief account which, at the same time, can serve as a reminder of many tasks pending in the mental health and human rights of sexual minorities, still victims of homophobia, stigma, and segregation, even more so in countries like Peru.